دراسة و تحليل تأثير الضجيج على حساسية المستقبل في نظام الاتصال الضوئي الرقمي - جورج, كابي (Latakia University Journal -Engineering Sciences Series, 2016)
يتضمن البحث دراسة وتحليل تأثير كلاَ من الضجيج الحراري، والضجيج الطلقي على حساسية المستقبل في نظام اتصال ضوئي رقمي، ويسلط الضوء على البارامترات التي تؤثر سلباً وإيجاباً على الحساسية، وقد تم استخدام اللغة البرمجية ماتلاب MATLAB لدراسة العلاقة بين حساسية المستقبل ومعدل المعطيات، وأوضحت مدى أفضلية حساسية المستقبل المحدود بالضجيج الطلقي من المستقبل المحدود بالضجيج الحراري؛ حيث تكون الحساسية أفضل بحدود 30dB. كما قدمت الدراسة توضيحاً لأفضلية الكاشف الضوئي APD من ناحية الحساسية مقارنة مع الكاشف الضوئي PIN بسبب ربحه الداخلي، وذلك عندما يكون الضجيج الحراري هو المهيمن، ولكن يفضل الـ PIN عندما يكون الضجيج الطلقي هو المهيمن.وتبين لنا من الدراسة تحسن حساسية مستقبل محدود بالضجيج الطلقي من أجل كفاءة كم أعلى ومن أجل طول موجة أكبر، ولكنها تسوء للحصول على معدل خطأ أصغر. كما أظهرت تحسن حساسية مستقبل محدود بالضجيج الحراري بزيادة الاستجابية وبزيادة مقاومة الحمل، ولكنها تسوء بزيادة رقم الضجيج وكذلك من أجل معدل خطأ أصغر. The effect of thermal noise and shot noise on the receiver sensitivity in a digital optical communication system will be studied and analyzed. Also, the positive and negative effects of Parameters on the receiver sensitivity will be highlighted. The programming tools (MATLAB) is used to study the relationship between the receiver sensitivity and bit rate. It showed that the shot-noise-limited receiver sensitivity is much better than the thermal -noise-limited receiver sensitivity with best 30dB. The study also provided an explanation for the preference of optical detector (APD) compared to that in (PIN) optical detector from sensitivity side due to its internal gain, this can be achieved when the thermal noise is dominant. However, the preference of optical detector(PIN) will be better in case of shot noise is dominant. Analyzed results show that there is a significant improvement in the shot-noise-limited receiver sensitivity for high quantum efficiency and high wavelength. However, the sensitivity is deteriorated to get a lower error rate. The thermal -noise-limited receiver sensitivity showed an improving by increasing the responsivity and the load resistance. However, it decreases by increasing the number of noise and the error rate.